Bound, free and in between: A review of pronouns in Ngarrindjeri in the world as it was. Issue 3 (3rd July 2021) - Gale, Mary-Anne; Amery, Rob; Simpson, Jane; Wilkins, David
ABSTRACT: Ngarrindjeri, a language from southern South Australia, is being revived on the basis of material recorded from 1840 until the 1960s. This material shows a heavy use of three types of pronouns, suggesting a language that is 'pronoun happy'. When reviving a language, it is essential to know how pronouns work, but the earliest source does not include the kinds of texts that allow analysis of how speakers use pronouns. Texts representing actual connected free speech in Ngarrindjeri are not attested until nearly a century later, by Ronald and Catherine Berndt and Norman Tindale. We compare the forms, meanings and second position distribution of Ngarrindjeri pronouns over time and across sources, considering dialect variation and language change. We show that the pronoun form-meaning pairs in texts recorded in the 1930s and 1940s are consistent with those recorded in the nineteenth century, and so we can have some confidence in using the Berndt and Tindale texts to reconstruct pronoun function. Confidence is further enhanced by showing the similarity in pronoun functions in texts recorded on the same topic from the same speaker, Albert Karloan, by the Berndts and Tindale. This review of Ngarrindjeri pronouns opens up possibilities for language revivalists.